Validation of an In vitro-in vivo Assay System for Evaluation of Transdermal Delivery of Caffeine - Farner, Fanni; Bors, Luca; Bajza, Ágnes; Karvaly, Gellért; Antal, István; Erdő, Franciska (Drug Delivery Letters, 2019)
Introduction: Degree of skin penetration of topical drugs and cosmetics is a crucial point concerning their effects and tolerability. For testing drug delivery across the dermal barrier different in vitro and in vivo assays have been developed. Caffeine has been shown to have beneficial effects against skin aging, sunburn and hair-loss, and it is protective against melanoma and non-melanoma type skin cancers. Aim of our study was to set up an assay system to evaluate caffeine penetration from topical formulation into the skin. Methods: Franz diffusion cells consisting of either a filter paper or an artificial membrane or rat skin were used as in vitro/ex vivo test systems and transdermal microdialysis in anaesthetized rats was performed as an in vivo assay. Results: Results indicate that Franz diffusion cell studies provide a good approximation of the release of caffeine from the formulation but are not able to differentiate between 2% and 4% cream concentrations. The maximum concentrations (Cmax) in case of the 2% cream formulation were 708.3 (2.7 μm pore), 78.7 (0.8 μm pore), 45.3 (0.45 μm pore) and 44.9 (rat skin) μg/7.5 mL, respectively. The in vivo microdialysis experiments were in accordance with the in vitro and ex vivo results and gave more information on the dynamics and follicular and transcellular phases of drug penetration through the layers of the skin. Discussion and Conclusion: Taken together, Franz diffusion cell and transdermal microdialysis are a good combination to evaluate caffeine release and penetration into the skin from the formulations tested. This system might also be used for rapid testing of other hydrophilic topical drugs and has a benefit in the prediction for human skin absorption and tolerability studies, in an early phase of drug development.
Keywords: skin penetration